The effect of business plans on business performance a case of selected SMEs in Ghana - Nkpaah, Mohammed Sadat (2016)
A thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology in Partial Fulfillment of Requirement for the award of degree of Master of Business Administration (strategic management consulting option).